The Aesthetics of Rhetorical Embellishments in the Poetry of Badiʿ al-Zamān al-Hamadhānī - Ruwaih, Balqes Khalaf (International Conference on Islamic Studies, 2025)
In this research, we shed light on the aesthetic values ​​of rhetorical devices in the poetry of Badī' al-Zaman al-Hamadhānī. We studied the most common devices, which are: alliteration, good division, quotation, and inclusion. It is worth noting that this poetry has not been given its due research and investigation of its artistic elements by scholars, as most studies have focused on studying the Maqamat of Badī' al-Zaman al-Hamadhānī.Upon reaching this stage, it is necessary to record the findings of my modest research. The poet frequently employed jinās (paronomasia) in his poetry, which had a significant impact on conveying his thoughts and meanings. His usage was not artificial but rather natural, with a particular emphasis on jinās nāqiṣ (imperfect paronomasia) and its various types, including taṣḥīf (orthographic wordplay), ishtiqāqī (derivative), muḍāriʿ (similar in form), and lāḥiq (suffixal). The art of ḥusn al-taqsīm (balanced division) also occupied a wide space in his works, valued for its harmonious quality and its profound effect on the audience, enabling him to structure and divide meanings effectively. Furthermore, like his predecessors and contemporaries, he employed iqtibās (quotation) and taḍmīn (inclusion); his quotations were often direct and explicit, while his use of taḍmīn involved incorporating verses or hemistiches from earlier poets without structural alteration. These practices not only enriched the poetic discourse of his dīwān but also revealed his extensive religious and literary reservoir, demonstrating to the audience the breadth of his cultural knowledge.